A Review of Semi-Quantum Secure Direct Communication Protocols - Meena, Kiran; Gupta, Narayan Lal; Mandot, Vivek (INFOCOMP Journal of Computer Science, 2025)
This review paper includes five distinct protocols in the field of semi-quantum secure direct communication based on different qubit carriers -single photons, EPR pairs, Cluster states, Mediated third party, and two degrees of freedom-polarisation and spatial mode. These protocols have been an- alyzed for their security against several methods of attack like- trojan horse attacks, intercept-resend Attacks, double C-not attacks, and modification attacks. Their efficiency is also estimated and described here. Future work direction in the field of SQSDC is summarised.